Trajetórias em diáspora : a experiência de universitárias haitianas de Belo Horizonte - Camila Rodrigues Francisco (2019)
The theme-field construction on this research landed from the observation of a selectivity on the treatment of foreign people in Brazil. Starting from the dialogue between a specific literature about diaspora, I adopted as a theoretical perspective the roots and ruts of the African diaspora, started by the forced dispersion of its habitants by the Americas and Caribe, conforming what today are identities and identifications very singular around a common point between all those experiences: the anti-black racism. In this sense, the main objective of this research was to think about the trajectories in diaspora of Haitian academic woman. In a more specific way: what does these trajectories of diaspora put as questions to the migration phenomenon? What about the places from where they came from and the places that they go? Which questions present themselves when we articulate the university as the place and the woman as the leading figure of this stage? This research was developed in my master’s degree in the postgraduate program of Psychology in the Federal University of Minas Gerais. The theme-field progressed by the participation in international academic community events, as much as conversations with black foreign students from some countries of Africa, and them, semi-structured interviews with the two Haitian woman mainly participants of this work. The experience of the African students led me to choose the Haitian woman by the initial field incursion combined by the access of the theme literature. I have noticed that there a few researches about the specific experience of the woman in this field. In addition, that a few studies approach the experience of the Haitian students but a lot is spoken about the Haitian migration for work and about the refugee situation that they might be included. Pursuing the suspect that the relations between Brazil and Haiti could reveal more about those absences; and that the articulation of gender as a category of analysis to the diaspora debate could produce important results, I brought as a central line the experience of two Haitian woman that were studying in two different universities in Belo Horizonte, a private one and a public one. I also established the differences between the concepts of diaspora and migration. Working with the diaspora identity idea brought by Edmund Gordon and Mark Anderson – inspired by the work of Stuart Hall and Paul Gilroy about diaspora – allowed me to come closer to a way in which the essentialism and the total hybridism were not part in the debate, which was, in this case: black diaspora, the African diaspora, and also the Haitian diaspora, the three main theoretical points that are articulated with the woman experience in the university.